Sustainability and outreach of microfinance institutions in Bangladesh: the role of governance - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (2019)
The purpose of this paper is to examine how selected governance indicators impact on performance measures of sustainability and outreach in microfinance institutions (MFIs) in Bangladesh. Compare four different sizes of MFIs, namely large, medium, small, very small, by focusing on their governance structure. The paper adopts a quantitative approach based on secondary data from conveniently sampled 655 microfinance institutions in Bangladesh. A panel data technique is employed as the essential analytical framework. It is shown that governance plays a critical role in the performance of MFIs and that the independence of the board and a clear separation of the positions of a CEO and board chairperson have a positive correlation with both performance measures. It would have been appropriate to have a more significant number of MFIs for the study. This limitation, however, does not compromise on the validity of the conclusions based on the findings of the study. In the context of multi-dimensional and sometimes conflicting objectives facing MFIs, an apparent balancing act of social objectives and institutional sustainability to ensure the adequate performance of MFIs is recommended. Studies on governance and its relationship with firm behaviour are limited, especially in Bangladesh. Its application in the microfinance sector with its peculiar characteristics is the added value of this paper.